Performance comparison of working with a database in Spring Boot version 3.2.3 and Laravel version 8.83.27 - Mateusz Zajączkowski (Journal of Computer Sciences Institute)
The subject of the article is the analysis of the efficiency of working with a database of applications created using programming frameworks: Spring Boot version 3.2.3 and Laravel version 8.83.27. Test applications were prepared in the REST API architecture, which examined the time efficiency of CRUD operations on the original database. Project structure and performance of test applications were compared. After analyzing the obtained results, it was found that in all scenarios, Spring Boot performed data operations on average 12 times faster.